Millimeter characteristics of Galactic and extragalactic starbursts - Santangelo, Gina <1980> (Alma Mater Studiorum - Università di Bologna, 2010)
The goal of the thesis was to compare Galactic and extragalactic star-forming environments, to understand whether we can derive scaling relations for the extragalactic star formation from our understanding of the Galactic star formation; and to analyze the effect of the angular resolution of the observations and the molecular tracer used in extragalactic studies. It is therefore necessary to perform observations at the same linear resolution in both cases. With this in mind we have started a program aimed at comparing properties of mini-starburst regions in our Galaxy and starbursts in nearby galaxies at similar linear resolutions.